Sex information and attitudes of 165 senior high school students with recommendations for the effective teaching of sex education - Tomaneng, Ester (Saturnino) ([Quezon City s.n.], 1966)
This study presents an evaluation on how a group of adolescents in high school get their information on sex and what attitudes have been developed as a result of the type and means of information. This was done by determining the following: the sex terms known by the students, sources of information, how environmental factors affect their knowledge of sex information, the ideas developed as a result of these environmental factors, and how sex information can be taught effectively.
Thesis (M.A.T.)--University of the Philippines
Keywords: Sex instruction